Improvement of thermal insulation of residential buildings' façades via acoustic insulation. Issue 2 (June 2016) - Paris-Newton, JAE; Prokofieva, E; Henry, N
The European community has been undertaking noise mapping of major cities and transportation routes over the last decade. Implementation of the action plan to achieve reduction in people noise exposure is a key aim of the European Noise Directive action planning. The French Environment and Energy Management Agency and Réseau Ferré de France combine their resources to reduce the noise exposure of noise sensitive receivers near railway lines. The acoustic insulation of façades near railway lines is quantified and improved if necessary. As part of these operations, a parallel improvement to the thermal performance of the façades is often possible, and may be incorporated into the acoustic mitigation designs. This article aims to evaluate the acoustic and thermal improvements achieved during an European Union pilot project concerned with the mitigation of freight train noise in three towns in the Rhône-Alpes region of France. Calculations of both the energy consumption and sound insulation of noise sensitive receiver façades prior to mitigation work are compared with measurements undertaken following the façade upgrades. This study focuses on a sampling of typical buildings built prior to 1978 (over 900 properties).